Molarity activity effect on mechanical and microstructure properties of geopolymer concrete: A review - Fatheali A. Shilar; Sharanabasava V. Ganachari; Veerabhadragouda B. Patil; T.M. Yunus Khan; Shaik Dawood Abdul Khadar (Case Studies in Construction Materials, 2022)
The purpose of this paper is to discuss the effect of different molarity, Alkaline to Binder ratio (A/B), and Sodium silicate to sodium hydroxide (SS/SH) ratios on the enhancement of fresh and mechanical properties of geopolymer concrete. In addition, it also reveals the investigation of recent trends and technology of developments of geopolymer concrete in recent years. The fresh and hardened properties like, slump, compressive, split tensile and flexural strength, water absorption, and bulk density of geopolymer concrete data for molarity variations ranging from 5, 8–18 M, with A/B ratios ranging from 0.30 to 0.5, and SS/SH ratios. These data further assessed using kernel density plot. Molarity and A/B ratio maximum the strength development of geopolymer concrete is computed from the graph. The various binding materials used and tests performed on geopolymer concrete by the researchers are also highlighted in this paper. Increasing the molarity and A/B ratios results in the strength development of geopolymer concrete up to a specific limit.Further increment of these parameters will not significantly affect the performance. The optimal value of molarity and A/B ratios at which give better performance is discussed in this paper. Structural performances of geopolymer concrete are higher than traditional concrete.